Resource scarcity and priority setting: from management to leadership in the rationing of health care? - Dickinson, H.; Freeman, T.; Robinson, Suzanne; Williams, I. (2011)
While continued interest in the application of priority-setting technologies is perhaps unsurprising in a time of austerity, they require sensitive implementation for their full potential benefits to be realized. This article looks at the role and value of leadership in addressing problems of a lack of perceived legitimacy and governance that have been raised in connection with the rationing enterprise. The potential and limitations of key leadership concepts such as ‘sense-making’ and ‘framing’ are explored, and notions of relational leadership and the importance of leading with political astuteness are discussed.